Experimental behaviour of reinforced concrete column models strengthened by CFRP materials - Kamiński, Mieczysław; Trapko, Tomasz (Journal of Civil Engineering and Management, 2006)
Strengthening of the reinforced concrete structures is one of the most difficult and important tasks of civil engineering. The paper presents the problem of strengthening of reinforced concrete structures. Experimental tests of load‐carrying capacity of reinforced concrete columns strengthened with CFRP strips and wraps have been carried out. The first objective of this research was to determine the influence of the type of reinforcement on load‐carrying capacity and strain. The second objective was to determine interdependence of the intensity of external reinforcement and load‐carrying capacity of element. Tests results have shown that the subject was worth investigating. Relations between external reinforcement ratio and load‐carrying capacity of small models of RC columns with various reinforcement ratio (from 1,4% to 4,2%) have been examined.Anglies pluoštu armuoto polimero lakštais sustiprintų gelžbetoninių kolonų eksperimentinis tyrimasSantrauka. Gelžbetoninių konstrukcijų stiprinimas – vienas iš sudėtingiausių ir svarbiausių statybinių konstrukcijų srities uždavinių. Straipsnyje nagrinėjama gelžbetoninių konstrukcijų stiprinimo problema. Čia pateikti anglies pluoštu armuoto polimero lakštais (CFRP) sustiprintų gelžbetoninių kolonų laikomosios galios eksperimentinių tyrimų rezultatai. Pirmasis tyrimų tikslas – nustatyti armatūros rūšies įtaką laikomajai galiai ir deformacijoms. Antrasis tikslas – nustatyti priklausomybę tarp išorinės armatūros intensyvumo ir elemento laikomosios galios. Bandymų rezultatai parodė tyrimų svarbą. Taip pat išnagrinėta priklausomybė tarp išorinės armatūros procento ir nedidelių gelžbetoninių kolonų su skirtingais armavimo procentais (nuo 1,4 % iki 4,2 %) laikomosios galios.Raktiniai žodžiai: kolona, gniuždymas, laikomoji galia, sustiprinimas, CFRP.First Published Online: 14 Oct 2010